Kommos : An Excavation on the South Coast of Crete ; The Kommos Region and Houses of the Minoan Town. Part I ; The Kommos Region, Ecology, and Minoan Industries - Shaw, Joseph W. (Princeton Legacy Library, 1995)
Cover -- Contents